A REVIEW ON FEMALE EXECUTIVE COMPENSATION GAP - Yingkun Lyu; Dr Irfah Najihah Binti Basir Malan (International Journal of Accounting, Finance and Business, 2022)
With the development of economy, women can be considered as an important part of labor force. However, gender difference has long been an important issue in workplace pay gap, how to gradually solve the gender pay inequity problem is a worldwide difficult problem, it is also one of the indicators to measure the economic development of a country or a region. When the perspective is focused on the gender difference in executive compensation, the gender pay gap still exists, however, research attention on this issue is not enough, so it is become a problem worth thinking about. Therefore, this paper focused on executive gender pay gap, the reasons are analyzed based on the current situation of gender differences in executive pay, and then several suggestions are highlighted to overcome these problems.